A new species of cardinalfish (Gymnapogon, Gymnapogonini, Apogonidae, Percomorpha) from the Philippines - Fraser, Thomas H. (Zootaxa, 2016)
The new species is consistent with Gymnapogon, a distinct genus having one to three spines on the preopercle edge, fused hypurals (parhypural+1+2 and 3+4+terminal central), a free fifth hypural, two epurals, no supraneurals, scaleless head and body, a single rod-like postcleithrum and complex lines of free neuromasts on the head, body and caudal fin. The new species is distinguished by having a combination of a rounded caudal with 15 branched principal caudal-fin rays, 2 unbranched principal caudal-fin rays, 10 soft dorsal rays with the anterior two rays unbranched, 9 or 10 anal rays with the first ray unbranched and 14 pectoral rays the lower three and upper two unbranched. Nominal species Gymnapogon          annona, G. foraminosus, G. japonicus, G. urospilotus and G. vanderbilti have 9 or 10 soft dorsal, 9 or 10 anal rays and 12 to 14 pectoral rays, the lower two and upper two unbranched. Gymnapogon africanus, G. melanogaster and G. philippinus have 9 soft dorsal rays, the first ray unbranched and 8 soft anal rays, the first ray branched. Gymnapogon japonicus has a rounded caudal fin with 13, 14 or 15 branched principal caudal rays. Gymnapogon africanus, G. annona, G. melanogaster, G. philippinus, G. urospilotus and G. vanderbilti have a forked caudal fin with 13 branched principal caudal rays and 2 unbranched upper and lower principal caudal rays. A single preopercle spine distinguishes the new species from the single bifid-like preopercle spine shared by Gymnapogon annona, G. melanogaster and undescribed forms. The wide-spread B-marked species complex made up of Gymnapogon urospilotus, G. vanderbilti and undescribed forms have at least one small upper preopercle spine in addition to the larger single spine near the angle of the preopercle.